Human Metapneumovirus (HMPV): Gambaran Klinis dan Tata Laksana: Tinjauan Pustaka - Situmorang, Theresia Murniwati (PT Kalbe Farma Tbk., 2025)
Human Metapneumovirus has recently gained global attention due to an outbreak in China. HMPV is an RNA virus of the Pneumoviridae family, a respiratory pathogen generally occuring seasonally and causes periodic epidemic. HMPV is transmitted through droplets, with the virus incubating for about three to five days, varying between individuals. Its symptoms are difficult to differentiate from symptoms by human respiratory syncytial virus (HRSV) infection. Common clinical symptoms experienced by HMPV patients include fever, cough, upper respiratory tract infection, or lower respiratory tract infection. HMPV can infect all age groups, but symptoms are more severe in infants, the elderly, and patients with comorbidities or immunosuppression. Real-time polymerase chain reaction (RT-PCR) remains the primary modality for diagnosing HMPV infection. Therapy is supportive as no vaccine or causal therapy is available, such as antipyretics, oxygen supplementation, and fluid hydration therapy. Several studies related to the management of HMPV are continued to be searched.